Raising interest in master of physical education during the COVID-19 pandemic: An analysis of Baidu Index data - Qinyi Tan; Meijie Wang; Luyan Teng; Fang He (Nicolaus Copernicus University in Toruń, 2022)
Objective: Current evidence shows the master of physical education has attracted attention since its opening. The study aims to quantify recent trends in the public interest and related online search behavior for master of physical education, and "nowcast" future scenarios with respect to the master of physical education. Methods: Baidu Index, a database of search engines with massive information, was employed. By searching for the keyword master of physical education, and using content analysis to understand the data information related to master of physical education. It extracted the search trend data regarding Chinese interest in the master of physical education from November 21, 2016, to November 21, 2022. Finally, it compares the search trend of search interests in the master of physical education with related terms. Results: It found that the search trend of master of physical education was on the rise overall. Specifically, the peak value appeared in September 2019, the valley value appeared around the Spring Festival each year, and the search trend in other periods was stable. Conclusion: The raise in public interest in a master of physical education will likely result in an increase in the number of candidates who are going to attend the National Graduate Entrance Exam to pursue a master of physical education. In the coming months or more, the competition for the employment of sports professionals in China will become more intense. Affected by the COVID-19, more people are interested in health and physical exercise, and then pay attention to the Master of Physical Education. The Sports Law of the People's Republic of China has been revised recently, which has led to more people interested in the master of physical education.